Analisis Komparatif Riwayat-Riwayat Hadis Tentang Pencegahan Penyakit Yang Terdapat dalam Sunan Ibn Majah dan Sunan Abi Daud - Muhammad Farhan; Prof, Dr. Dahlia Lubis, M.Ag Lubis (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to comparatively analyze hadith narrations concerning disease prevention in Sunan Ibn Mājah and Sunan Abī Dāwūd, focusing on their similarities, differences, narration quality, and meanings from the perspective of Islamic health. This qualitative study employed a library research approach. Primary data consisted of hadiths related to disease prevention in both collections, while secondary sources included hadith commentaries, rijāl al-ḥadīṡ literature, hadith studies, and Islamic health references. Data were collected through documentation and analyzed comparatively through identification, classification, assessment of narration quality, and interpretation of hadith meanings. The findings demonstrate that both Sunan Ibn Mājah and Sunan Abī Dāwūd contain narrations emphasizing preventive principles in maintaining health, particularly through cleanliness, dietary regulation, avoidance of disease sources, and environmental hygiene. These similarities indicate that the Prophetic guidance places prevention before the development of disease. Differences were identified in hadith wording, chains of transmission, the quality of some narrations, and the systematic placement of hadiths within each collection. Analysis of the hadith commentaries further shows that disease prevention encompasses physical, psychological, social, and spiritual dimensions. Therefore, the two hadith collections provide complementary preventive principles that contribute to a holistic understanding of health from an Islamic perspective